2004
DOI: 10.1016/j.femsim.2004.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in NOD2, Crohn's disease, and susceptibility to pulmonary tuberculosis

Abstract: The nucleotide oligomerization binding domain 2 gene (NOD2) encodes an intracellular receptor for bacterial components, which is expressed in monocytes and is associated with Crohn's Disease (CD). This finding, along with epidemiological evidence, supports a role for infection in the pathogenesis of CD. Speculation that mycobacteria are involved in CD led us to investigate NOD2 in susceptibility to tuberculosis (TB), a global public health problem caused by Mycobacterium tuberculosis. CD-associated NOD2 varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 21 publications
1
19
1
Order By: Relevance
“…Recent genotyping studies of TB patients showed no significant association of six single-nucleotide polymorphisms in the leucine-rich repeat domain of NOD2 or of eight single-nucleotide polymorphisms in the Card15 promoter region with pulmonary TB in two different African populations, indicating that, at least in the populations studied, Card15 is not a major susceptibility gene for TB (26,34). …”
Section: Discussionmentioning
confidence: 86%
“…Recent genotyping studies of TB patients showed no significant association of six single-nucleotide polymorphisms in the leucine-rich repeat domain of NOD2 or of eight single-nucleotide polymorphisms in the Card15 promoter region with pulmonary TB in two different African populations, indicating that, at least in the populations studied, Card15 is not a major susceptibility gene for TB (26,34). …”
Section: Discussionmentioning
confidence: 86%
“…33 Known genetic polymorphisms explain only about 20% of the associated risk of CD. 34 Therefore, other factors, genetic and/or environmental, could contribute to CD susceptibility. The concept of an environmental trigger in the etiology of this disease is supported by the increased development of CD in the new immigrant generations.…”
Section: Discussionmentioning
confidence: 99%
“…However, although Gandotra et al (2007) found that the macrophages and DCs of NOD2-deficient mice were impaired in their production of proinflammatory cytokines and nitric oxide following infection with live Mtb, their study provided strong evidence that NOD2 was not essential for host defence in a murine infection model. Furthermore, genotyping of patients with tuberculosis found no significant association between polymorphisms in the leucinerich repeat domain of NOD2 or in the Card15 gene that encodes NOD2 with pulmonary TB in two different African populations, suggesting that Card15 is not a major TB susceptibility gene (Stockton et al, 2004;M€ oller et al, 2007).…”
Section: Innate Pathogen Recognition Receptorsmentioning
confidence: 94%